Upaya Peningkatan Kesejahteran Keluarga Melalui Pemberdayaan pada Kelompok Perempuan Sido Makmur di Desa Pasrujambe - Nurdiyanto, Dwi; Hariyono, Syech; P, Pairan (e-Sospol, 2017)
Abstract This research was aimed at describing and analyzing the efforts devoted to escalating family prosperity through empowerment on Sido Makmur of woman community in Pasrujambe village. Research question under investigation was germane to how the efforts devoted to improving family prosperity on Sido Makmur woman community were carried out to improve the prosperity of families in Pasrujambe village. The presence of empowerment carried out in Sido Makmur community was one a kind of farming-based woman community which was intended to rally the appreciations of farming women. The research method operative in the study was descriptive, which was coupled with qualitative approach. The research site was Pasrujambe village, Pasrujambe sub-district of Lumajang district. Research informants were determined by purposive sampling, leading to including primary and secondary informants. To gain research data, observation, interview, and documentation were operationalized. Upon testing data validity, the researcher applied source trianglation. Research findings revealed that the empowerment to household women was done by enacting Sido Makmur woman community, through which various soft skill and hard skills trainings were given. As a corollary, such undertakings exerted benefits to family prosperity in the form of economy improvement, knowledge improvement, and improvement.